The impact of a community social marketing campaign on children's meal orders and consumption: main outcomes from a group randomised controlled trial - Erin Hennessy; Eleanor Shonkoff; Linda Harelick; Peter Bakun; Kenneth Chui; Susan Roberts; Sara Folta; Jeanne Goldberg; Christina D Economos (Cambridge University Press, 2023)
Abstract Objective: Restaurants may be important settings for interventions to reduce children's energy intake. The objective of this study was to test the impact of a parent-focused social marketing campaign to promote healthy children's meals on calories ordered and consumed by children at quick-service restaurants (QSR). Design: Using a repeated cross-sectional study design, two urban communities were randomised to intervention (IN) v. control (C) condition. A community-wide social marketing campaign was implemented in the IN community to empower Black and Latinx mothers who frequent QSR (priority population) to select healthier options for their child. Setting: Data were collected in 2016 at QSR located within the communities pre- and post-IN and analysed in 2017. Participants: Parents (n 1686; n 819 and n 867 for I and C conditions, respectively) were recruited after placing their QSR order; a survey, receipt and their child's leftovers were collected. Results: Calories ordered did not differ significantly between the IN and C conditions (changeadj = -146·4 kJ (-35·0 kcal); 95 % CI -428·0 kJ (-102·3 kcal), 134·6 kJ (32·2 kcal)). In a sub-analysis of only the priority audience, children in the IN community ordered significantly fewer calories compared to C children in unadjusted models (changeunadj = -510·4 kJ (-122·0 kcal); 95 % CI -1013·4 kJ (-242·2 kcal), -7·5 kJ (-1·8 kcal)), but the trend did not persist after adjusting for covariates (changeadj = -437·2 kJ (-104·5 kcal); 95 % CI -925·5 kJ (-221·2 kcal), 50·6 kJ (12·1 kcal)). Calories consumed followed similar trends. Conclusion: The campaign did not significantly reduce children's QSR calories ordered or consumed. However, a quantitatively important mean reduction in calories was suggested among the priority audience, indicating potential for community-wide promotion of healthful children's meals.